MODELOS DE GOVERNANÇA UTILIZADOS POR INCUBADORAS DE EMPRESAS ÂNCORAS DURANTE PROJETOS EM REDE: ESTUDO DE CASO DO PROJETO FINEP/PNI-2006 - Salgado, Alexandre Dutra (2009)
This study highlights the importance of business incubators in the strategic context to promote technological innovation, we look at the governance model used by business incubators anchors of Rio de Janeiro, PUC-RIO Genesis Institute, business incubator COPPE / UFRJ and Polo's Biotechnology BIO Rio Rio de Janeiro / UFRJ for network projects FINEP / PNI. Delimited as research incubators see how anchors adapt their own models of governance to manage projects online. The intent of the study is to analyze the relevance of models that are implemented in incubators anchor during the project FINEP / PNI, how the actions of the incubators surveyed relationships with other incubators satellites, the importance of this context FINEP. Incubators (Bio River, COPPE and GENESIS) have had relevant work in the technological development and transforming ideas into business despite the difficulties of operating in the network, this work is a reflection of what happens in everyday life such as incubators may be seen through this research.